Prevalence and dynamics of antibodies against Toxoplasma gondii in kids born from naturally infected goats. Issue 5 (October 2015) - Rahman, Moizur; Alauddin, Md.; Hossain, K.M. Mozaffor; Islam, Md. Hemayetul; Kitoh, Katsuya; Nagamune, Kisaburo; Takashima, Yasuhiro
Abstract: We investigated the presence of antibodies against Toxoplasma gondii in domesticated goats intended for human consumption in a rural suburb of Rajshahi, Bangladesh. Antibodies to T. gondii were found in 55.1% (80/145) of the goats tested in our sample. The seroprevalence among goats aged < 1 year, 1–2 years, 2–3 years and ≥ 3 years were 36.7%, 66.0%, 59.1% and 100%, respectively. Our results demonstrated that seroprevalence increased with age. Among the seropositive goats, a subsample of eight free-ranging female goats with access to male goats was placed under continuous observation. During the observation period, these seropositive female goats delivered 11 kids, all of which were found to be seronegative before suckling colostrum. This finding strongly suggested that trans-placental infection rarely occurs in female goats that have acquired an infection before pregnancy. Our results indicate that infection via ingestion of oocysts plays a more important role than endogenous trans-placental infection in maintaining the endemicity of T. gondii among goats in Bangladesh. Graphical abstract: Highlights: Seroprevalence of T. gondii among goats in Bangladesh increased with age. 11 kids born from a T. gondii latently infected dam was seronegative. Endogenous trans-placental infection of T. gondii is not common in goats.